Data-Driven Decision Making in MSMEs: Leveraging Free Analytics Tools for Financial Planning and Efficiency - Pertiwi, Joana Putri; Hana, Afrida Ummu (Journal of Management and Informatics, 2025)
As a key enabler of enhancement in financial performance and sustainability, Data-Driven Decision-Making (DDDM) within the digital transformation discourse has been helpful for MSMEs. It is unfortunate that in many developing economies, MSMEs become hindered by informal practices due to limited resources, low digital literacy, and complicated perceptions of analytics tools. In this study, we will investigate the practical application of free digital platforms- Microsoft Excel, Google Data Studio, and Canva Analytics support financial planning and operational efficiency in MSMEs. The research applies a descriptive-applicative approach to create realistic financial data representing the fictitious operations of an MSME-from daily sales, operational costs, to promotional expenses over 30 days. Results show that simple dashboards can lead to some critical insights, for instance, weekly net cash flow that peaked at IDR 2,150,000 in Week 3 and IDR 1,980,000 in Week 5, which means greater operational efficiency. A simulated digital promotion campaign saw a Return On Investment (ROI) of 220%, thereby reinforcing the importance of sales and marketing analytics. Furthermore, the operational expense accounted for about 65% of the total expenses, thus showing room for cost optimization. The findings substantiate the fact that with a little training, MSMEs can now take their financial decisions away from intuition and into data-driven decisions using tools that are freely available online. This study presents a framework that is replicable and scalable in the same resource-constrained environments, with enough practical insights for policymakers and MSME development programs who wish to promote digital financial literacy and performance monitoring.